Impact of personalized embryo transfer based on endometrial receptivity assay on pregnancy outcomes in women with recurrent implantation failure: a retrospective study - Yarasi, Padmalatha; Rajesh, Rekha; Jain, Meenakshi; Desireddy, Sahithya; Pattubala, Indhumathi; Yemme, Preetam R.; Rajesh, Varshikha; Rajesh, Varnikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Recurrent implantation failure (RIF) poses a persistent challenge in assisted reproductive technology (ART), characterized by the repeated inability to achieve pregnancy following multiple embryo transfers. This retrospective study aimed to assess the impact of personalized embryo transfer (PET) guided by the endometrial receptivity assay (ERA) on pregnancy outcomes in couples experiencing RIF. Methods: The study included couples who had undergone two or more failed ICSI cycles despite transferring grade A blastocyst. Endometrial biopsies were obtained during standard HRT cycles and analyzed using the ERA, a genomic diagnostic tool that evaluates the transcriptomic signature of the endometrium to pinpoint the window of implantation (WOI). Subsequent PET cycles were tailored based on ERA results, categorizing patients into receptive, pre-receptive, or post-receptive phases. Results: Our findings revealed that 69.81% of patients were receptive, while 22.64% were pre-receptive and 7.55% were post-receptive. Following ERA-guided PET, 93.94% of patients achieved pregnancy, with a live birth rate of 80.65%. These results underscore the potential of this personalized approach to enhance ART success in challenging cases of RIF. Conclusions: These results contribute to advancing personalized medicine in reproductive health, emphasizing the importance of individualized treatment strategies based on the precise assessment of endometrial receptivity.